Financial sustainability of united territorial communities and land management: state and problems - Novakovsky, L.; Tretyak, A.; Dorosh, Y. (Land Management, Cadastre and Land Monitoring, 2019)
It is grounded that in order to improve the financial condition of the created united territorial communities, land management measures should be implemented in order to establish their boundaries and land management of the territories, which, as land improvements, will increase the cost of land and, accordingly, revenues to the budget from the payment for land. To determine the legal and organizational principles of land management of the united territorial communities, proposals were made for amending the current legislation. Key words: land management, schemes of land management, territory of united territorial communities, land use, land management, land payment.